2020
DOI: 10.1186/s13046-020-01667-y
|View full text |Cite
|
Sign up to set email alerts
|

The IL1β-IL1R signaling is involved in the stimulatory effects triggered by hypoxia in breast cancer cells and cancer-associated fibroblasts (CAFs)

Abstract: Background: Hypoxia plays a relevant role in tumor-related inflammation toward the metastatic spread and cancer aggressiveness. The pro-inflammatory cytokine interleukin-1β (IL-β) and its cognate receptor IL1R1 contribute to the initiation and progression of breast cancer determining pro-tumorigenic inflammatory responses. The transcriptional target of the hypoxia inducible factor-1α (HIF-1α) namely the G protein estrogen receptor (GPER) mediates a feedforward loop coupling IL-1β induction by breast cancer-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 93 publications
4
44
0
Order By: Relevance
“…Hence, estrogenic GPER signaling fosters CAFs to produce a variety of secreted factors that fuel proliferation, migration, invasion, spreading, and EMT of nearby BC cells, as well as tubulogenesis in endothelial cells ( De Francesco et al, 2013 ; Yuan et al, 2015 ; De Marco et al, 2016 ; Pisano et al, 2017 ; Cirillo et al, 2019 ; Santolla et al, 2019 ). In particular, the functional interaction of GPER with the EGFR, IGF1R, FGFR1, HIF-1α, and Notch transduction pathways may trigger the release of growth factors, such as CTGF, VEGF, and FGF2, and cytokines such as IL-1β that account for important paracrine actions mediated by CAFs toward BC growth and dissemination ( Pandey et al, 2009 ; De Francesco et al, 2013 , 2014 , 2017 , 2018a ; Pupo et al, 2014 ; Ren et al, 2015 ; De Marco et al, 2016 ; Santolla et al, 2019 ; Lappano et al, 2020b ). Interestingly, diverse studies have shown that GPER bridges together estrogenic signaling with IGF1R and IR-mediated action in the breast tumor microenvironment, independent of the ER status.…”
Section: Microenvironmental Interactions Between Estrogenic Signals Amentioning
confidence: 99%
“…Hence, estrogenic GPER signaling fosters CAFs to produce a variety of secreted factors that fuel proliferation, migration, invasion, spreading, and EMT of nearby BC cells, as well as tubulogenesis in endothelial cells ( De Francesco et al, 2013 ; Yuan et al, 2015 ; De Marco et al, 2016 ; Pisano et al, 2017 ; Cirillo et al, 2019 ; Santolla et al, 2019 ). In particular, the functional interaction of GPER with the EGFR, IGF1R, FGFR1, HIF-1α, and Notch transduction pathways may trigger the release of growth factors, such as CTGF, VEGF, and FGF2, and cytokines such as IL-1β that account for important paracrine actions mediated by CAFs toward BC growth and dissemination ( Pandey et al, 2009 ; De Francesco et al, 2013 , 2014 , 2017 , 2018a ; Pupo et al, 2014 ; Ren et al, 2015 ; De Marco et al, 2016 ; Santolla et al, 2019 ; Lappano et al, 2020b ). Interestingly, diverse studies have shown that GPER bridges together estrogenic signaling with IGF1R and IR-mediated action in the breast tumor microenvironment, independent of the ER status.…”
Section: Microenvironmental Interactions Between Estrogenic Signals Amentioning
confidence: 99%
“…As a key gene associated with CAFs, CALD1 showed strong correlations with stromal and immune scores, suggesting its dual regulation of stromal and immune components. Also, CALD1 exhibited essential involvements in the processes modulating the TME, including EMT (32), hypoxia (33), extracellular matrix remodeling (34) and cytokine regulation (35), as revealed by GSEA. Moreover, CALD1 represented a positive correlation with M2 macrophages and a negative correlation with CD8+ T cells.…”
Section: Discussionmentioning
confidence: 97%
“…Both HIF-1ɑ and HIF-2ɑ promote a more invasive phenotype [ 33 ], by activating the epithelial-mesenchymal transition (EMT) program [ 34 36 ] or cooperating with other strong pro-invasive factors such as Met receptor and soluble hepatocyte growth factor (HGF) [ 37 ], or VEGF receptor (VEGFR)/VEGF [ 38 ]. Notably, in triple negative breast cancer (TNBC) HIF-1ɑ stimulates the relase of the typical pro-inflammatory cytokine IL-1β that induces a metastatic attitude in both tumor cells and cancer associated fibroblasts (CAFs), creating a TME that strongly favors metastatization [ 39 ]. In addition, HIF-1ɑ also promotes a tumor-tolerant environment, reducing the infiltration of CD4 + and CD8 + T-lymphocytes and tumor-associated macrophages (TAMs) [ 40 ], increasing the differentiation of T-lymphocytes into T-helper 17 (TH17) cells [ 41 ] and modulating TAM polarization [ 42 ].…”
Section: Background: the Impact Of Hypoxia On Cancer And Its Microenvmentioning
confidence: 99%